Prevalence and correlates of sexual intimate partner violence among trans women in the San Francisco Bay Area - Santos, Glenn-Milo; McFarland, Willi; Wilson, Erin C. (Frontiers in Global Women's Health, 2025)
BackgroundIntimate partner violence (IPV), including sexual IPV, is a significant public health issue with serious mental, physical, and economic consequences. Trans women are disproportionately affected by sexual IPV. However, research on factors associated with sexual IPV is limited among trans women. This study seeks to identify factors associated with sexual IPV in a large cohort of trans women in the San Francisco Bay Area.MethodsWe conducted a secondary data analysis of data from the Trans*National cohort study (2016–2017), which enrolled 629 trans women via respondent-driven sampling; we conducted bivariate and multivariable logistic regression analyses to examine correlates of lifetime history of sexual IPV.ResultsThe prevalence of lifetime sexual IPV was 36%, and bivariate analyses identified several factors associated with sexual IPV, including inconsistent hormone use, non-prescribed hormone use, sex work, polysubstance use, depression, posttraumatic stress disorder, suicidality, homelessness, and discrimination. Multivariable models revealed significant associations between sexual IPV and psychosocial factors, such as substance use, mental health diagnoses, and experiences of violence and discrimination.ConclusionThese findings are consistent with the substance abuse, violence, and HIV/AIDS syndemic framework, underscoring the interconnectedness of these conditions among trans women. In addition, the findings suggest that disruptions in access to gender-affirming care may be a negative consequence of sexual IPV. These results also highlight the urgent need for integrated approaches to address the mental health, substance use, and HIV prevention needs of trans women who experience sexual IPV. Interventions that address structural discrimination and provide holistic support are necessary to improve the health and wellbeing of trans women survivors of sexual IPV.